TAXES ON TOBACCO IN SOLVING THE PROBLEMS OF PROMOTING HEALTH OF THE POPULATION - Баран, Ольга Ивановна; Григорьев, Юрий Аркадьевич (Medicine in Kuzbass, 2017)
The progressive increase in taxes on tobacco products plays a huge role in reducing tobacco harm to health of the population. In Russia, the share of the tax burden on the retail tobacco price is still low.Subject. Dynamics of tobacco taxation.Objective. Studying the role of tobacco taxes in the effective solution of problems of health promotion.Methods. Analysis of the legislative acts on protecting citizens’ health from the effects of exposure to environmental tobacco smoke and consequences of tobacco use in the Russian Federation and abroad, studying data on taxes on tobacco products.Main results. The inability of the state to increase the price of tobacco products in the wake of rising the disposable income has led everywhere to increased demand for tobacco products, to increase in the burden of irrecoverable losses of the population. Effective tobacco taxation will be a good step in the Russian social and demographic policy.Conclusions. In Russia, a set of measures should be developed, which includes: 1) an increase in the tax on tobacco products; 2) wide dissemination of the information on the dangers of smoking; 3) ubiquitous restrictions on smoking in public places; 4) a ban on tobacco advertising. Consistent increase in the taxes on tobacco will allow rising budget revenues, creating price barriers for tobacco use, saving a significant part of the population from the disease burden and premature irreversible losses.
Keywords: health of the population; tobacco products; tobacco taxes